Microglia Dystrophy Following Binge-Like Alcohol Exposure in Adolescent and Adult Male Rats - Marshall, S. Alex; McClain, Justin A.; Wooden, Jessica I.; Nixon, Kimberly (Frontiers in Neuroanatomy, 2020)
Microglia are dynamic cells that have roles in neuronal plasticity as well as in recovery responses following neuronal injury. Although many hypothesize that hyperactivation of microglia contributes to alcohol-induced neuropathology, in other neurodegenerative conditions disruption of normal microglial processes also contributes to neuronal loss, particularly as microglia become dystrophic or dysfunctional. Based on the observation of a striking, abnormal morphology in microglia during binge-like ethanol exposure, the present study investigated the impact of excessive ethanol exposure on microglia number and dystrophic morphology in a model of alcohol dependence that includes neurodegeneration in both adult and adolescent rats. Following 2- and 4-day binge ethanol exposure, the number of microglia were decreased in the hippocampus and the perirhinal and entorhinal cortices of both adult and adolescent rats. Furthermore, a significant number of microglia with a dystrophic morphology were observed in ethanol-exposed tissue, accompanied by a significant decrease in brain-derived neurotrophic factor expression in the hippocampus. Together these findings suggest another means by which microglia may contribute to alcohol-induced neurodegeneration, specifically dystrophic microglia and/or loss of microglia may disrupt homeostatic and recovery mechanisms. These results demonstrate that microglia also degenerate with excessive alcohol exposure, which has important implications for understanding the role of microglia - and specifically their contributions to plasticity and neuronal survival - in neurodegenerative disease.